NEUROPROTECTIVE ACTIVITY OF NOVEL CUR-CA-THIONE AND ITS OXIDATIVE STRESS STUDY - Shelat, Devang Y.; Acharya, Sanjeev R. (International Journal of Pharmacy and Pharmaceutical Sciences, 2016)
Objective: Alzheimer's disease a progressive neurodegenerative disorder affected by the formation of amyloid beta and tau proteins. Medicinal plants have been proved significantly for its anti-oxidant and anti-inflammatory activity that might help in treating neurological disorders. Curcumin has been hugely studied in the treatment of various ailments but its water solubility and bioavailability is still a concern but we have tried to exterminate the problem by our formulation CUR-CA-THIONE. Now, we have expanded the study of CUR-CA-THIONE for its neuroprotective estimation by evaluating behavioral, biochemical and histopathological assessment in rats. Methods: Wistar rats of either sex (M/F: 25-350g; 350-450 g) were selected for study and divided into 8 groups. All animals except NC were given aluminum chloride via oral route throughout the study period (30 d) while group 3-8 received treatment one-hour post aluminum chloride induction from 15th day to 30th day. One week prior to the start of the experiment all animals were given training for behavioral assessment through y-maze and morris water maze with the weekly assessment. On 30th-day post completion of study rat brain was isolated to study biochemical and histopathological examination. Results: The results of the behavioral assessment in CUR-CA-THIONE complex showed an increase in total arm entries in Y-maze and decrease in time duration for morris water maze test. A significant (p<0.01) decrease in lipid peroxidation, superoxide dismutase, acetylcholine and total protein levels in formulations while significant (p<0.01) increase in glutathione and catalase level was observed. Conclusion: The given formulation shows that curcumin-casein-glutathione complex shows potential action as a neuroprotective effect. Â 